Antibacterial Activity Assay on Escherichia coli of The Active Fraction Matoa Seeds (Pometia Pinnata J.R Forst & G. Forst.) - Karnelasatri, Karnelasatri; Yacob, Iren Anggreni; Andareas, Pangeran; Santoso, Feronia Reni Cyrena; Novia, Jessica (Universitas Tadulako, 2024)
One of the plants had been used as a medicinal plant in Papua is Pometia Pinnata J.R Forst & G. Forst or the Matoa plant. The aim of this study is to determine the antibacterial activity of the active fraction of Matoa seeds against Escherichia coli bacteria. The positive control and negative control used were ciprofloxacin and dimethyl sulfoxide, respectively. 96% ethanol solvent was used to extract the simplicia of Matoa seeds. Fractionation was carried out using n-hexane, ethyl acetate and water as solvents. The Kirby Bauer diffusion method was used in the antibacterial activity assay at concentrations of 100 mg/mL, 200 mg/mL, 300 mg/mL, 400 mg/mL, and 500 mg/mL. Overall, the inhibition zones obtained from the sequential concentrations above were 8.89 mm, 10.18 mm, 10.34 mm, 10.84 mm, and 11.76 mm respectively. Further, data analysis was performed with One Way ANOVA and the results showed significant differences between concentrations. Data analysis was then continued with the post hoc Tukey HSD test and a concentration of 500 mg/mL was concluded as the optimum concentration.